2015
DOI: 10.1177/1475090215586638
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on interference effects and wetted area pattern of asymmetric planing catamarans

Abstract: Asymmetrical planing catamarans are increasingly used in moderate to very high-speed applications due to some tempting qualities such as less wetted surface and better seakeeping behavior. The present numerical study attempts to provide new insight into hydrodynamics of such vessels by highlighting the distinguishing aspects and employing novel appropriate approaches to deal with them. A systematic investigation has been carried out on a prismatic geometry at various demihull separations (including zero separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Hence the two ends of the spectrum were the minimum of 0.09 and the maximum of 1.0. Intriguingly, the case of s/L = 0 was also reported by some researchers examined the interference effects at high Froude numbers including Savitsky and Dingee [41], Sherman [45] (who studied 0 < s/L < 0.33), Liu and Wang [42], Lee [44], and [57].…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Hence the two ends of the spectrum were the minimum of 0.09 and the maximum of 1.0. Intriguingly, the case of s/L = 0 was also reported by some researchers examined the interference effects at high Froude numbers including Savitsky and Dingee [41], Sherman [45] (who studied 0 < s/L < 0.33), Liu and Wang [42], Lee [44], and [57].…”
Section: Methodsmentioning
confidence: 63%
“…Although two-dimensional analysis of water entry problem has provided precious information for planing catamarans, investigation in three dimensions presents new insight into and reveals more realistic findings of interference effects. Yengejeh, Amiri, Mehdigholi, Seif and Yaakob [57] applied three dimensional Computational Fluid Dynamics (CFD) to solve Reynolds-Averaged Navier Stokes (RANS) equations in order to determine the flow field around a prismatic asymmetric planing catamaran. They examined interference effect on viscous, pressure, air, and water resistance separately and found that at very high speeds the viscous and air components are as important as the pressure and water resistance, besides both the lift force and the wetted surface, also known as the pressure area [43], increased by decreasing demi-hulls separation.…”
Section: Introductionmentioning
confidence: 99%
“…Lately, Computational Fluid Dynamics (CFD) has imposed itself as a very valuable tool for many numerical studies related to the investigation of the total resistance of a catamaran and the interference phenomenon. [12][13][14][15][16][17][18][19][20] The combination of experimental and computational fluid dynamics currently represents the best practice for the investigation of catamaran hydrodynamics. 21 The influence of a bulbous bow on the total resistance of a yacht was investigated using both towing tank tests and numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…With the fast development of computer science and numerical methods, computational fluid dynamics (CFD) has become a feasible approach with sufficient accuracy to investigate ship hydrodynamics [21]. Various CFD solvers have been applied to examine the calm water resistance and seakeeping of both monohulls [22][23][24] and multihulls [25][26][27][28][29]. A combined experimental and numerical study was carried out by Zaghi et al [30] to analyse the interference effects between the demihulls and the dependency on the separation of a high-speed catamaran.…”
Section: Introductionmentioning
confidence: 99%